2019
DOI: 10.3390/jcm8050615
|View full text |Cite
|
Sign up to set email alerts
|

Migration of the Lag Screw after Intramedullary Treatment of AO/OTA 31.A2.1-3 Pertrochanteric Fractures Does Not Result in Higher Incidence of Cut-Outs, Regardless of Which Implant Was Used: A Comparison of Gamma Nail with and without U-Blade (RC) Lag Screw and Proximal Femur Nail Antirotation (PFNA)

Abstract: The best intramedullary nail for the treatment of unstable AO/OTA 31.A2.1-3 fractures remains uncertain. A total of 237 patients (45 male, 192 female) were eligible for the assessment with an average age of 81.9 ± 10.5 years and a minimum follow-up of six months. We assessed the cut-out rate, the TAD and calTAD (Tip Apex distance) of three different implants. An overall cut-out rate of 2.5% (n = 6) was observed. The cut-out rate was 1.2% (n = 1) in the Proximal Femur Nail Antirotation (PFNA) group, 3.7% (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…The frequency of age-associated bone fractures is expected to rise as life expectancy continues to increase [2]. The principle factor responsible for this trend is the age-related bone demineralisation of the proximal femur compounded by the high prevalence of vitamin D deficiency [3]. Furthermore, these changes are compounded by the higher rates of falls among the elderly [4].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of age-associated bone fractures is expected to rise as life expectancy continues to increase [2]. The principle factor responsible for this trend is the age-related bone demineralisation of the proximal femur compounded by the high prevalence of vitamin D deficiency [3]. Furthermore, these changes are compounded by the higher rates of falls among the elderly [4].…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ the additional U-Blade lag screw reduced the cut-out rate compared with the standard lag screw (2.2% vs. 3.7%). In addition, they found that the cut-out rate in PFNA remained the smallest (1.2%) compared with Gamma3 with or without an additional U-Blade lag screw, although the PFNA showed significant migration within the femoral head 32 . However, they did not describe and compare the BMD, details of fracture patterns such the presence of a basicervical component and comminution of the anterior cortex, and quality of reduction, which can affect fixation failures such as cut-out.…”
Section: Discussionmentioning
confidence: 99%
“…Both RoSA and the Gamma-RC hip screw systems have proved to increase significantly the migration resistance compared with single screw systems [5,8,11,12] . However, the clinical results, mainly presented by retrospective studies, did not show a conclusive picture in this regard to date [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%